Pleomorphic Adenoma: Report of Five Cases - Shilpa J Parikh; Pritesh Ruparelia (Wolters Kluwer Medknow Publications, 2007)
Pleomorphic Adenoma (P A), the most common benign tumor of salivary gland, is common to occur in parotid gland and the submandibular gland. However, as far as minor salivary glands are concerned, the most common site is hard palate and very few cases are reported to occur in soft palate. In the present case report, one case found in soft palate, three cases involving hard palate and one case is found extra orally involving submandibular gland. All the cases were diagnosed on the basis of clinical features. CT Scan report (as in case I) and confirmed by histopathological report. The patient was given palliative radiotherapy due to poor cardiac condition of the patient. Other cases were treated with surgical excision. Follow up examination of all five cases was done for different durations. No re-occurrence was reported.